1996
DOI: 10.1128/aem.62.7.2615-2620.1996
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Volatile Fatty Acids on Nitrite Accumulation by a Pseudomonas stutzeri Strain Isolated from a Denitrifying Fluidized Bed Reactor

Abstract: Intermediate nitrite accumulation during denitrification by Pseudomonas stutzeri isolated from a denitrifying fluidized bed reactor was examined in the presence of different volatile fatty acids. Nitrite accumulated when acetate or propionate served as the carbon and electron source but did not accumulate in the presence of butyrate, valerate, or caproate. Nitrite accumulation in the presence of acetate was caused by differences in the rates of nitrate and nitrite reduction and, in addition, by competition bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(73 citation statements)
references
References 27 publications
3
68
2
Order By: Relevance
“…Different volatile fatty acids used as carbon sources have also been shown to influence nitrite accumulation in Ps. stutzeri (van Rijn et al 1996), and pH influences the process in Paracoccus denitrificans (Kučera 1986). Körner and Zumft (1989) found that nitrate inhibition of nitrite reductase could lead to a nitrite build up in Ps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different volatile fatty acids used as carbon sources have also been shown to influence nitrite accumulation in Ps. stutzeri (van Rijn et al 1996), and pH influences the process in Paracoccus denitrificans (Kučera 1986). Körner and Zumft (1989) found that nitrate inhibition of nitrite reductase could lead to a nitrite build up in Ps.…”
Section: Discussionmentioning
confidence: 99%
“…stutzeri, a known denitrifier, which is widely disseminated in many environments (e.g. van Rijn et al 1996). It possesses the full complement of denitrifying enzymes and is therefore capable of producing inert nitrogen as the end product.…”
Section: Introductionmentioning
confidence: 99%
“…In pH 5.0, 4.0, 3.5 and 3.0 groups, the final nitrite concentrations were 16.32, 12.99, 9.87 and 4.92 mg L À1 , respectively. Van Rijn et al (1996) reported a similar result that the nitrite could not accumulate in butyric acid, valeric acid and hexanoic acid. The degradation of nitrite in acid environment could be attributed to disproportionation reaction between NO À 2 and H + (Knipp et al, 2011), and the reaction equation was described as follows: Fig.…”
Section: Resultsmentioning
confidence: 72%
“…Paracoccus sp. was isolated from a £uidized-bed reactor used for nitrate removal in intensive ¢sh-culture systems [7]. In addition to heterotrophic denitri¢cation on a wide array of organic substrates, the strain exhibited autotrophic denitri¢cation in the presence of reduced sulfur compounds (unpublished results).…”
Section: Bacterial Strain Plasmids and Growth Conditionsmentioning
confidence: 97%
“…Its intermediate formation during the denitri¢cation process is in£uenced by a number of factors. Among those: (i) elevated oxygen levels [3,4], (ii) shifts in pH values [5], (iii) nitrate concentrations [6,7], (iv) nitrate starvation [8], (v) light exposure [9], and (vi) the presence of phosphate [10].…”
Section: Introductionmentioning
confidence: 99%